(3a-7)(4a-b-2)-(3a+4b)(3a+4b)=

Simple and best practice solution for (3a-7)(4a-b-2)-(3a+4b)(3a+4b)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3a-7)(4a-b-2)-(3a+4b)(3a+4b)= equation:


Simplifying
(3a + -7)(4a + -1b + -2) + -1(3a + 4b)(3a + 4b) = 0

Reorder the terms:
(-7 + 3a)(4a + -1b + -2) + -1(3a + 4b)(3a + 4b) = 0

Reorder the terms:
(-7 + 3a)(-2 + 4a + -1b) + -1(3a + 4b)(3a + 4b) = 0

Multiply (-7 + 3a) * (-2 + 4a + -1b)
(-7(-2 + 4a + -1b) + 3a * (-2 + 4a + -1b)) + -1(3a + 4b)(3a + 4b) = 0
((-2 * -7 + 4a * -7 + -1b * -7) + 3a * (-2 + 4a + -1b)) + -1(3a + 4b)(3a + 4b) = 0
((14 + -28a + 7b) + 3a * (-2 + 4a + -1b)) + -1(3a + 4b)(3a + 4b) = 0
(14 + -28a + 7b + (-2 * 3a + 4a * 3a + -1b * 3a)) + -1(3a + 4b)(3a + 4b) = 0

Reorder the terms:
(14 + -28a + 7b + (-6a + -3ab + 12a2)) + -1(3a + 4b)(3a + 4b) = 0
(14 + -28a + 7b + (-6a + -3ab + 12a2)) + -1(3a + 4b)(3a + 4b) = 0

Reorder the terms:
(14 + -28a + -6a + -3ab + 12a2 + 7b) + -1(3a + 4b)(3a + 4b) = 0

Combine like terms: -28a + -6a = -34a
(14 + -34a + -3ab + 12a2 + 7b) + -1(3a + 4b)(3a + 4b) = 0

Multiply (3a + 4b) * (3a + 4b)
14 + -34a + -3ab + 12a2 + 7b + -1(3a * (3a + 4b) + 4b * (3a + 4b)) = 0
14 + -34a + -3ab + 12a2 + 7b + -1((3a * 3a + 4b * 3a) + 4b * (3a + 4b)) = 0

Reorder the terms:
14 + -34a + -3ab + 12a2 + 7b + -1((12ab + 9a2) + 4b * (3a + 4b)) = 0
14 + -34a + -3ab + 12a2 + 7b + -1((12ab + 9a2) + 4b * (3a + 4b)) = 0
14 + -34a + -3ab + 12a2 + 7b + -1(12ab + 9a2 + (3a * 4b + 4b * 4b)) = 0
14 + -34a + -3ab + 12a2 + 7b + -1(12ab + 9a2 + (12ab + 16b2)) = 0

Reorder the terms:
14 + -34a + -3ab + 12a2 + 7b + -1(12ab + 12ab + 9a2 + 16b2) = 0

Combine like terms: 12ab + 12ab = 24ab
14 + -34a + -3ab + 12a2 + 7b + -1(24ab + 9a2 + 16b2) = 0
14 + -34a + -3ab + 12a2 + 7b + (24ab * -1 + 9a2 * -1 + 16b2 * -1) = 0
14 + -34a + -3ab + 12a2 + 7b + (-24ab + -9a2 + -16b2) = 0

Reorder the terms:
14 + -34a + -3ab + -24ab + 12a2 + -9a2 + 7b + -16b2 = 0

Combine like terms: -3ab + -24ab = -27ab
14 + -34a + -27ab + 12a2 + -9a2 + 7b + -16b2 = 0

Combine like terms: 12a2 + -9a2 = 3a2
14 + -34a + -27ab + 3a2 + 7b + -16b2 = 0

Solving
14 + -34a + -27ab + 3a2 + 7b + -16b2 = 0

Solving for variable 'a'.

The solution to this equation could not be determined.

See similar equations:

| -6/7= | | y/2-12=11 | | b-4/5=9/10 | | 0.50x+0.05(10-x)=0.10(-49) | | 25=3+2x+5x+4 | | 5a+13=6a-5 | | -3-y=-15 | | 7n^2+37n+20=4n | | 4X(w+3)=w-15 | | y=10x+140 | | -4(3x-1)-2x+5=121 | | 200.96=3.14*D | | 2a+5b=7 | | 7u/5=42 | | X=1.571428571 | | 400x+200=350x+850 | | 9e^11x=11 | | -3x+-5=2x | | 270.04=3.14*D | | 9(x-9)=-18 | | 2x+76=90 | | 10.50=1.50+2n | | 5(2y-4)=-10 | | 2.6=x/(2-2x) | | 5x+24=3 | | -(-7x-5)+8x-10= | | 2x+5(5x-14)=97 | | 14*20-6(20+3)=20+9 | | 2/3=10/e | | 5x-4x=-6x+4 | | 3(7x+2)(x-1)=0 | | =56x^7+21x^4+63x^3 |

Equations solver categories